Competitiveness of oil crops production: evidence from Serbia - Matkovski, Bojan; Ðokić, Danilo; Zekić, Stanislav; Jurjević, Žana (Frontiers in Sustainable Food Systems, 2025)
After cereals, oil crops are the most important group of crops in the world, and in Serbia, sunflower and soybeans, as well as their products, have the largest share in production and foreign trade of oil crops. Serbia is practically the leader in the Western Balkan region in the production of oil crops. Considering that in the last few years there have been various disturbances in the world market of oil crops, the aim of this paper is to look at the competitive positions of Serbia. In this direction, the production and foreign trade tendencies will be estimated, and the positions on the world market will be determined by the methods of revealed comparative advantages and level of specialization. The results of the research show that the competitive position of oil crops from Serbia on the international market is satisfactory, and it is primarily exported to the markets of the European Union and CEFTA countries. Oil crops make up about 10% of agri-food export from Serbia, and the best comparative advantages are observed in sunflowers, both sunflower oil and sunflower seeds. When it comes to the integration of the oil crops market with the world market, the highest degree of integration is observed with the countries of the European Union, with which the largest volume of exchange of these products is also carried out.